Organizational behavior in sport management : an applied approach to understanding people and groups - Barnhill, Christopher R.; Smith, Natalie L.; Oja, Brent D. (Palgrave Macmillan, 2021)
This textbook presents a comprehensive analysis of organizational behavior in sport organizations from a practitioner's perspective. It covers issues related to managing employees and work teams as well as organizational structure and culture in sport. The book has four sections: Organizational Behavior in the Sports Industry, Getting to Know Employees and Volunteers of Sport Organizations, Work Groups and Teams, and Understanding the Organization. Each chapter begins with a practitioner interview describing a challenge that was overcome by their organization. That example is used to highlight applicable theories and interventions used in the industry. Additional examples or theories are discussed to provide students a broad picture of managerial issues in the sports industry and provide alternative approaches to intervention illustrated in the practitioner interview. The case studies offer the opportunity to practice and apply the ideas to real-world scenarios in the sports industry. Students using this book will gain an understanding of how managers and leaders apply theory to communicate with and engage employees to foster desired organizational cultures while being challenged to address common issues using cases and hypothetical situations.- Resumé vydavatel
Keywords: sportovní organizace; organizační chování; personální management; sports organization; organizational behavior; personnel management; elektronické knihy; učebnice; electronic books; textbooks